Barreras percibidas para el uso del condón y conducta sexual protegida en jóvenes de Chihuahua, México - Jiménez -Vázquez, Vicente (2025)
Introduction: More than 40 years after the emergence of HIV, it represents a global public health problem. Currently, condom use is the main means of protection, however the literature indicates that its use among young people is low. Objective: To determine the relationship between perceived barriers to condom use and protected sexual behavior in young people.  Material and Methods: This study was descriptive-correlational. The population consisted of young people from Chihuahua, Mexico. The sample was 129 and convenience sampling was used. Data collection was done online, and a sociodemographic and sexuality data sheet and two standardized subscales were used. Results: The means of barriers to condom use was 13.5 (SD = 5.64), indicating that young people perceive few barriers to condom use. The means of protected sexual behavior was 39.4 (SD = 17.8), that is, young people have a low level of condom use. Barriers to condom use were identified as being negatively and significantly related to protected sexual behavior (rs = -0.255, p < 0.01). Conclusion: The findings of the study confirmed the presence of individual barriers and the statistically significant relationships between these and condom use, knowing these limitations will allow them to be considered by health professionals in promoting the correct and consistent use of this means of protection.